Efeito do recobrimento de filmes de carbono tipo diamante depositados a plasma na manutenção do torque de parafusos protéticos - Lepesqueur, Laura Soares Souto [UNESP] (2014)
Objective: To evaluate the values of reverse torque RT ( % ) of prosthetic screws titanium alloy coated with a film of diamond-like carbon (DLC) and DLC film doped with diamond particles (CD- DLC) comparing them with screws without treatment (control). Method: Sixty implants were divided into six groups according to the type of connection (external or internal hex) and type of abutment screw (n = 10 ): Group A1: external hexagon / screw control , Group A2: external hexagon / screw with DLC; group A3: external hexagon / screw with CD- DLC; group B1: internal hex / screw control; group B2: internal hex / screw with DLC; group B3: internal hex / screw with CD- DLC. The DLC films and CD - DLC were deposited by PECVD process (Plasma Enhanced Chemical Vapour Deposition). The implants were inserted into polyurethane resin, and crowns of nickel chrome cast were cimented and the abutments screwed into the implants. The reverse torque was measured after the mechanical cycling (1.106 cycles). Statistical analysis was performed by one factor ANOVA and Tukey's test, with significance level of 5%. Analysis was performed screws through scanning electron microscopy (SEM) before and after loading . Results: The results showed that after mechanical reverse torque RT (%) for the untreated group (A1) was significantly higher than the one of the DLC groups (A2) and CD -DLC (A3) (p = 0.0001). However, there was no statistical difference for the groups with and without coating in maintaining torque for the screws’ internal hex connections (p = 0.5476). Conclusion: After mechanical cycling, the diamond-like carbon with and without doping of diamond on the screws for abutments, showed no improvement in maintaining the torque in external and internal hex connections...